Fingolimod Leads to Immediate Immunological Changes Within 6 h After First Administration - Sehr, Tony; Akgün, Katja; Haase, Rocco; Ziemssen, Tjalf (Frontiers in Neurology, 2020)
Objective: Multiple effects of fingolimod have already been describe. Here we investigated the acute effects on immune cell subsets and identified correlations with autonomic first dose phenomena and long-term immunological effects. Methods: Blood samples of 20 MS patients were analysed using FACS. Immune cell frequencies before and at defined prospective time points beginning 6 hours after first fingolimod administration were evaluated in parallel to cardiovascular autonomic and clinical. Results: A significant decrease of absolute lymphocyte count (1.81GPt/l to 1.42GPt/l), CD3+ (1.34GPt/l to 1.06GPt/l), CD3+CD4+ (0.94GPt/l to 0.73GPt/l) and CD19+ (0.26GPt/l to 0.19GPt/l) cells could be already demonstrated within 6 hours after first dose which correspond to a relative reduction by 28%, 23%, 23% resp. 29% in relation to the longterm steady state cell frequency level. Short- and long-term effects were significantly correlated for lymphocytes, CD3+, CD3+CD4+, CD3+CD8+, CD19+, CD14+ and NK cells as well as for neutrophil granulocytes. In addition, correlations could be found between reduced heart rate (68.95bpm to 60.05bpm) and the decrease in CD3+, CD3+CD4+ and CD19+ cells after 6 hours. Conclusions: Early immunological changes could already be detected 6 hours after fingolimod first dose. Most of the acute changes correlate with long-term modulation. A link between the acute immunological and cardiological effects was found.